2008
DOI: 10.1590/s0103-84782008000800008
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de métodos de agrupamento para o estudo da divergência genética em cultivares de feijão

Abstract: IVComparação de métodos de agrupamento para o estudo da divergência genética em cultivares de feijão ABSTRACT The aim of this research was to compare cluster methods, on the basis of the dissimilarity (standardized average euclidian and Mahalanobis generalized) and obtain information on genetic diversity in common bean cultivars (Phaseolus vulgaris). Fourteen common beans cultivars were evaluated in nine experiments conducted in Santa Maria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 5 publications
2
16
0
6
Order By: Relevance
“…Cargnelutti et al (2008), by the analysis of 14 bean cultivars, reported estimates which were higher, as they observed a correlation of 0,90 either for the Mahalanobis distance, or for the Euclidean distance. In the dendrogram generated from the Mahalanobis and the Euclidiana distances, the cuts were made in a level of 50% of dissimilarity, agreeing with Santos et al (2013) and Torres et al (2015), who used the same percentage of dissimilarity to observe the group formation in soybean genetic diversity study.…”
Section: Resultsmentioning
confidence: 92%
“…Cargnelutti et al (2008), by the analysis of 14 bean cultivars, reported estimates which were higher, as they observed a correlation of 0,90 either for the Mahalanobis distance, or for the Euclidean distance. In the dendrogram generated from the Mahalanobis and the Euclidiana distances, the cuts were made in a level of 50% of dissimilarity, agreeing with Santos et al (2013) and Torres et al (2015), who used the same percentage of dissimilarity to observe the group formation in soybean genetic diversity study.…”
Section: Resultsmentioning
confidence: 92%
“…Sanglard et al (2013), using a set of 126 SSR (simple sequence repeat) and 677 single nucleotide polymorphism (SNP) markers, estimated the genetic distance between Rudá and AND 277 as 78.6 and 71.3%, respectively. Cargnelutti Filho et al (2008) also split an Andean cultivar and 12 other Mesoamerican cultivars by hierarchical and Tocher methods based on the Mahalanobis generalized distance matrix. Veloso et al (2015) used molecular markers to assess genetic dissimilarity among cultivars and showed that the greatest difference belonged to the Black/Mesoamerican and Streaked/Andean types.…”
Section: Discussionmentioning
confidence: 99%
“…Os dados foram padronizados e a distância escolhida foi a euclidiana média, devido à ausência de repetições nos tratamentos. O método de agrupamento escolhido foi o método da ligação completa, o qual tem tendência a formar grupos compactos (CARGNELUTTI FILHO et al, 2008).…”
Section: Análise Estatísticaunclassified